Impact of Terrorism on Trade: A Case of North-East Nigeria - Ribadu, Abubakar Bashir (School of Social Sciences, 2015)
This explanatory study investigates the impact of terrorism on trade in North-East Nigeria. It further shows the empirical investigation of the scenario in which continuous mayhem posed by the ‘Boko Haram’ insurgent group has caused Nigeria loss in revenue over the past six years. Government has so far failed in it’s strive to provide the citizens with adequate security for life and properties, as well as an enabling environment for trade and investments which can also positively stimulate its revenue as a nation. As, there are numerous impacts of terrorism in Nigeria, trade is one of the key to the North-East region as their major source of income as well as revenue to the government. The study will use secondary data and will be guided by frustration-aggression theory to connect facts and give a meaningful context. Hence, the findings are expected to indicate possible relationship between terrorism and trade in the North-Eastern region. To this end, while applying the frustration-aggression theory, the researcher will propose some possible policy recommendations to the government on how to halt the menace threatening its revenue base, traders and investors. Keywords: ‘Boko Haram’, Terrorism, Frustration-Aggression Theory, North-Eastern Region, Trade